Trinidad and Tobago - Parkinson, Norman (My University, 2010)
The postcard shows guests by the pool at the Crowne Reef Hotel in Tobago. Description printed on the back of the postcard: "Crown Reef Hotel, Tobago where the blue of the fresh-water pool matches the colour of the sea."
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Postcards; Hotels; Swimming pools; Trinidad and Tobago